Penerapan Orthopneic Position terhadap frekuensi napas pada pasien TB paru di ruang Isolasi Kohort - Rini Marlina; Novita Elisabeth Daeli; Sanny Frisca (Lembaga Pengembangan Kinerja Dosen, 2026)
Pulmonary Tuberculosis is a disease cause an infection by Mycobacterium tuberculosis which attacking the lungs. The problem that often appears is Respiratory system disorder that this symptomatically happens with shortness. Shortness occurs due to an imbalance between oxygen demand and supply, thereby increasing respiratory effort and reducing patient comfort. A non-pharmacological measure to reduce shortness of breath is orthopnea positioning.This therapy aims to increase lung expansion, improve ventilation, and relax the respiratory muscles, thereby helping to reduce Asphyxiate in patients with pulmonary tuberculosis. To determine the effectiveness of orthopneic positioning in reducing dyspnea in patients with pulmonary tuberculosis. Case study design with 3 respondents who were placed in the orthopneic position for 5 minutes with a stopwatch used to measure respiratory rate The results of this study show that the orthopneic position is effective in reducing shortness of breath, as evidenced by Mr. R, who had a respiratory rate of 24 breaths per minute before being placed in the orthopnea position. After being placed in the orthopneic position, his respiratory rate decreased to19 breaths per minute. Mr. K's respiratory rate was 24 breaths per minute before being placed in the orthopneic position and decreased to 20 breaths per minute after being placed in the orthopneic position. Mr. M's respiratory rate was 24 breaths per minute before being placed in the orthopneic position and decreased to 19 breaths per minute after being placed in the orthopneic position